Socioeconomic and cultural drivers of women's formal work in rural Ghana - Elena Groß; Raymond Boadi Frempong (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
We study socioeconomic indicators of female labour force participation in off-farm formal employment in a subsistence agriculture setting in northern Ghana, where a new commercial farm provides a positive demand shock for low-skilled labour. We use a set of quantitative and qualitative data examining determinants of female labour force participation, the social effects arising from it, and the influence on female decision-making power in their households. In line with other micro-studies, we find that education is not a driver of female labour participation in low-skilled jobs. Women from wealthier households and those with young children have a significantly lower probability of starting off-farm work. Polygamy and male dominance reduce women's labour force participation. Women who earn off-farm income are strengthened in their intra-household decision-making position and can spend more money on themselves.
Keywords: I31; J10; J20; 330; female labour participation; Ghana; intra-household decision-making; off-farm work; polygamy